Transforming African agricultural markets through digital innovations: What we (do not) know - Abay, Kibrom A.; Abate, Gashaw T.; Chamberlin, Jordan; Kassim, Yumna; Spielman, David J.; Tabe-Ojong, Martin Paul Jr. (International Food Policy Research Institute, 2022)
This policy note synthesizes the key messages and lessons from existing evidence and trends in the development, deployment and scale up of ICT-enabled marketing tools. It is based on the recently published discussion paper titled “Digital tools and agricultural market transformation in Africa: Why are they not at scale yet, and what will it take to get there”. Key messages • Many digital innovations have been developed and deployed in recent years in Africa, many of which have only been implemented at pilot stages, with limited evidence of successful scaling. • There remains significant marketing and institutional constraints hindering the development of some of these digital innovations, which may further explain disparate progress in countries. • Differential access to digital innovations across genders and different typologies of households may trigger alternative variants of digital divide. • Although the landscape of digital innovations in Africa offers several reasons to remain optimistic, the prevailing disconnect between pilots and scale-ups merits further evaluation.